2007
DOI: 10.1111/j.1442-2050.2007.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase inhibitor improves postoperative clinical courses after thoracic esophagectomy

Abstract: Sivelestat sodium hydrate is a selective inhibitor of neutrophil elastase (NE), and is effective in acute lung injury associated with systemic inflammatory response syndrome (SIRS). The effect of Sivelestat for postoperative clinical courses after transthoracic esophagectomy was investigated. Consecutive patients with carcinoma of the thoracic esophagus who underwent transthoracic esophagectomy between 2003 and 2004 were assigned to the Sivelestat-treated group (n = 18), and those between 1998 and 2003 were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 41 publications
(101 reference statements)
4
56
0
Order By: Relevance
“…These elevated levels correlate with the severity of the lung injury (103,104). Moreover, small clinical trials provided evidence for the protective effect of elastase inhibition (105)(106)(107)(108). Furthermore, administration of elastase induces lung damage in murine models of ALI (109-111) whereas elastase inhibition attenuated the development of ALI (112)(113)(114)(115)(116) (Table 1).…”
Section: Neutrophil-derived Serine Proteasesmentioning
confidence: 99%
“…These elevated levels correlate with the severity of the lung injury (103,104). Moreover, small clinical trials provided evidence for the protective effect of elastase inhibition (105)(106)(107)(108). Furthermore, administration of elastase induces lung damage in murine models of ALI (109-111) whereas elastase inhibition attenuated the development of ALI (112)(113)(114)(115)(116) (Table 1).…”
Section: Neutrophil-derived Serine Proteasesmentioning
confidence: 99%
“…Sato et al reported that steroid use significantly reduces the incidence of postoperative pneumonia (23). Furthermore, the efficacy of NEI, a selective inhibitor of neutrophil elastase, used for preventing postoperative pneumonia in esophagectomies has been evaluated (25,26). Suda et al concluded that the duration of postoperative SIRS after esophagectomy, the duration of mechanical ventilation, and the length of ICU stay were significantly shortened in NEI-treated patients (25).…”
Section: Variablesmentioning
confidence: 99%
“…Furthermore, the efficacy of NEI, a selective inhibitor of neutrophil elastase, used for preventing postoperative pneumonia in esophagectomies has been evaluated (25,26). Suda et al concluded that the duration of postoperative SIRS after esophagectomy, the duration of mechanical ventilation, and the length of ICU stay were significantly shortened in NEI-treated patients (25). In their study, Ono et al reported that the preventive administration of NEI reduced the rate of postoperative SIRS in patients with severe conditions on mechanical ventilation after esophagectomy (26).…”
Section: Variablesmentioning
confidence: 99%
“…Several animal and clinical studies have revealed its ability to restore various types of tissue injuries as well as aspiration pneumonia (6), hepatoenteric ischemia (7), ALI (8) and lung injury associated with SIRS in humans (9). Recently, it has been reported that post-operative sivelestat administration after transthoracic esophagectomy improved the pathophysiological condition of SIRS and the post-operative clinical course even in patients without complications, as well as the deterioration of the PaO 2 (arterial oxygen tension)/FIO 2 (inspired oxygen fractional concentration) ratio in the post-operative period following esophagectomy (10,11). however, its prophylactic effect on transthoracic esophagectomy is still unknown.…”
Section: Introductionmentioning
confidence: 99%